TEAM INCLUSION AND EMPOWERMENT AMONG NURSING STAFF IN LONG-TERM CARE. (16th November 2018) - Barry, T; Longacre, M
Abstract: The prevalence of Alzheimer's disease and other dementias will continue to increase as the U.S. population ages, exacerbating the need for long-term care in both home and residential care settings. Further, team-based approaches to care have become more apparent as part of the landscape in residential care facilities in an effort to improve staff performance and resident outcomes vis-à-vis empowering direct care staff. This purpose of this study was to characterize the perceptions of inclusion or the extent licensed and unlicensed nursing staff (N=95) felt included as a care team member by others, including co-workers, supervisors and non-nursing clinicians. Given the emphasis on inter-disciplinary teams, a secondary goal was to explore if greater internal and external inclusion was correlated with heightened empowerment and its related dimensions using the Perceptions of Empowerment Instrument (Roller, 1988). Further, regression analyses revealed that levels of total empowerment, autonomy, responsibility and participation vary according to how included team members felt and by whom. This information can influence how long-term care organizations structure team building activities among staff to create truly empowered workers. These findings shed light on the importance of tailoring staff training to target specific team members in order to increase a sense of empowerment that aligns with the specific dimension(s) associated with the targeted group. Increasing empowerment along all dimensions may have a positive influence on job outcomes which, in turn, can result in higher quality of care.